Temperature-mediated inhibition of a bumblebee parasite by an intestinal symbiont - Palmer-Young, Evan C. (Proc Biol Sci, 2018)
Competition between organisms is often mediated by environmental factors, including temperature. In animal intestines, nonpathogenic symbionts compete physically and chemically against pathogens, with consequences for host infection. We used metabolic theory-based models to characterize differential responses to temperature of a bacterial symbiont and a co-occurring trypanosomatid parasite of bumblebees, which regulate body temperature during flight and incubation. We hypothesized that inhibition of parasites by bacterial symbionts would increase with temperature, due to symbionts having higher optimal growth temperatures than parasites. We found that a temperature increase over the range measured in bumblebee colonies would favour symbionts over parasites. As predicted by our hypothesis, symbionts reduced the optimal growth temperature for parasites, both in direct competition and when parasites were exposed to symbiont spent medium. Inhibitory effects of the symbiont increased with temperature, reflecting accelerated growth and acid production by symbionts. Our results indicate that high temperatures, whether due to host endothermy or environmental factors, can enhance the inhibitory effects of symbionts on parasites. Temperature-modulated manipulation of microbiota could be one explanation for fever- and heat-induced reductions of infection in animals, with consequences for diseases of medical and conservation concern.